Do landscape structural and functional units exist? - J. F. Reynolds; Jianguo Wu (Integrating Hydrology, Ecosystem Dynamics, and Biogeochemistry in Complex Landscapes, 1999)
The complexity of landscapes requires that simplified constructs or frameworks be developed for understanding and predictions. Toward this goal, the question is posed, "Do landscape structural and functional units exist?" The argument is in favor of the existence of landscape units, but acknowledge that there are no generic recipes for simplifying the real world for use in landscape models. While simplification is the key to achieving understanding and prediction, explicit consideration of scale multiplicity in studying complex landscapes is dictated by the hierarchical properties of landscapes. Therefore, we suggest that the hierarchical patch dynamics paradigm provides a conceptual framework to accomplish these objectives.
//NMSU,USDA//LTER III//ProCite field[6]: InProCite field[36]: In
Keywords: biogeochemistry, ecosystem dynamics; biogeochemistry, hydrology; book; books; chapter; chapters; hydrology, biogeochemistry; hydrology, ecosystem dynamics; landscape, biogeochemistry; landscape, ecosystem dynamics; landscape, hydrology; model, landscape; report; reports